Randomized Comparison of 3 Hemostasis Techniques After Transradial Coronary Intervention. Issue 5 (September 2016) - Cong, Xiaoliang; Huang, Zhigang; Wu, Jia; Wang, Jiamei; Wen, Feng; Fang, Lingling; Fan, Min; Liang, Chun
Abstract : Background: The transradial route for coronary intervention has proven to be a safe and feasible method, and several techniques have been shown to be effective in achieving hemostasis. Objectives: The aim of this study is to evaluate the efficacy of 3 hemostasis techniques on radial artery outcomes after transradial catheterization. Methods: A total of 1650 patients were randomly assigned to 1 of the 3 hemostasis techniques after the procedure. The outcome measures were local vascular complications, tolerance to the device, and the time taken to achieve hemostasis. Results: Time taken to achieve hemostasis was significantly longer in the pressure dressing (PD) group than in the pneumatic compression device (PCD) group and rotary compression pad device (RCD) group (306 ± 65 vs 263 ± 62 and 237 ± 58 minutes; P < .0001). There were also significant differences between PD, PCD, and RCD groups with respect to the incidence of oozing (8.2% vs 5.1% and 5.1%; P = .047) and discomfort level (1.68 vs 1.43 and 1.40; P < .0001). The incidence of early (24 hours after the procedure) radial artery occlusion was significantly higher in the PD group than in the PCD and RCD groups (15.6% vs 5.8% and 4.5%; P < .0001). Logistic regression analysis showed that independent predictors of radial artery occlusion at 30-day follow-up visit were diabetes (hazard ratio, 2.39), larger radial artery diameter (hazard ratio, 0.52), the use of the PCD (hazard ratio, 0.51, compared with PD) and the RCD (hazard ratio, 0.52, compared with PD), and radial artery patency during compression (hazard ratio, 0.016). Conclusions: Hemostasis devices have comparative advantages over the conventional pressure dressing. The presence of radial artery flow during compression represents a strong predictor of radial artery patency during follow-up periods.